The Role of Glycemic Load, Dairy, and Fatty Acids in Acne Disorders: A Systematic Review and Meta-Analysis - Claudia Felicia Limanda; Asya Mathlubaa; Ferdian Harum Istikanto; Sisca; Yusra Nabila; Shania Rizky Amalia; Syafira Ayudiah Syah Putri; Tasya Khalis Ilmiani; Ericko Hartanto; Melinda Nurfadhila (Medicinus, 2025)
Background: Modern dietary patterns characterized by high glycemic load, dairy consumption, and imbalanced fatty acid profiles may aggravate acne through insulin, IGF-1, and inflammatory pathways. However, findings across studies remain inconsistent. This systematic review and meta-analysis aimed to evaluate the associations between dietary glycemic load, glycemic index, dairy intake, and fatty acid composition with acne disorders. Methods: Following PRISMA 2020 guidelines, PubMed, EMBASE, and Scopus were systematically searched to September 2025. Eligible human studies assessing quantitative relationships between these dietary exposures and acne risk or severity were included. Random-effects meta-analyses were performed using the Hartung–Knapp–Sidik–Jonkman method, with effect sizes expressed as standardized mean differences (SMD) or risk ratios (RR). Result: Five studies encompassing 716 participants (426 acne, 290 controls) met the inclusion criteria. Pooled estimates indicated no significant associations for glycemic load (SMD = 0.09; 95% CI −0.30 to 0.49), glycemic index (SMD = 0.09; 95% CI −0.30 to 0.49), fatty acids/adiponectin (SMD = 0.11; 95% CI −0.74 to 0.97), or dairy consumption (RR = 1.04; 95% CI 0.25 to 4.25). Heterogeneity ranged from moderate to high (I² = 65–90%). Certainty of evidence was moderate for glycemic and dairy outcomes, and low for fatty acids. Conclusions: No significant pooled associations were observed between dietary glycemic load, dairy intake, or fatty acids and acne risk. Despite biological plausibility linking diet to acne via hormonal and inflammatory mechanisms, evidence remains inconsistent. Larger, controlled trials are warranted to define the role of nutritional interventions in acne management.